Efektifitas Senam Knee Chest Position Terhadap Kehamilan Sungsang Di Klinik Ar-Rahim Kec. Carenang Kab. Serang Banten - Masri Masri; Riza Faulina (Malahayati Nursing Journal, 2024)
ABSTRACT Breech pregnancy causes a high risk of morbidity and mortality. Most breech pregnancies end in a Caesarean section. In a cephalic pregnancy, the head, which is the largest part of the fetus, is born first, whereas in a breech position, the largest part of the fetus is born last. Birth of the head in the breech position does not have a "Maulage" mechanism because the structure of the basic bones of the head is tight and dense, so it only takes 8 minutes after the baby's body is born. Limited time for delivery of the head and not having a maulage mechanism can result in high infant mortality. The care given is by doing the Knee chest position or the chest-knee position, which is a menstrual position which aims to change the fetal position back to normal. To determine the effectiveness of knee chest position exercises for breech pregnancies at the Ar-Rahim Clinic, Kec. Carenang District. Attack Banten in 2023.This research uses a quasi-experiment with a Non-Equivalent Control Group Design approach. This design is almost the same as the pre-test and post-test with control group design. The sampling technique used a total sampling technique so that the number of samples in this study was 30 respondents. The instruments in the research were data from pregnant women in the third trimester at the Ar-Rahim Clinic and a questionnaire that had been prepared and the analysis in this research used the Wilcoxon test.The Wilcoxon test results show the effectiveness of knee chest position exercises for breech pregnancies with a significance value of 0.05, namely 0.001 at the Ar-Rahim Clinic, Kec. Carenang District. Attack Banten in 2023. It is hoped that this research can be applied to the management of breech pregnancies using knee chest position exercises as an effort to change the position of the fetus to normal for oneself, family and relatives. Keywords: Knee Chest, Exercise, Pregnant Women in Breech Position  ABSTRAK Kehamilan sungsang menyebabkan resiko morbiditas dan mortalitas yang tinggi. Sebagian besar kehamilan sungsang berakhir dengan operasi Caesar. Pada kehamilan dengan letak kepala, bagian kepala yang merupakan bagian terbesar janin lahir terlebih dahulu, sedangkan pada letak sungsang bagian terbesar janin akan lahir terakhir. Persalinan kepala pada letak sungsang tidak mempunyai mekanisme “Maulage” karena susunan tulang dasar kepala yang rapat dan padat, sehingga hanya mempunyai waktu 8 menit, setelah badan bayi lahir. Keterbatasan waktu persalinan kepala dan tidak mempunyai mekanisme maulage dapat menimbulkan kematian bayi yang besar. Asuhan yang diberikan yaitu dengan melakukan Knee chest position atau posisi dada-lutut merupakan posisi menungging yang bertujuan untuk merubah kembali posisi janin menjadi normal. Untuk mengetahui efektifitas senam knee chest position terhadap kehamilan sungsang di Klinik Ar-Rahim Kec. Carenang Kab. Serang Banten tahun 2023. Penelitian ini menggunakan quasi eksperimen dengan pendekatan Non Equivalent Control Group Design. Desain ini hampir sama dengan pre-test and post-test with control group design. Teknik pengambilan sampel menggunakan teknik total sampling sehingga jumlah sampel dalam penelitian ini adalah 30 responden. Instrumen pada penelitian berupa data ibui hamil trimester III yang beirada di Klinik Ar-Rahim dan kuieisioneir yang suidah disuisuin dan analisis penelitian ini menggunakan uji Wilcoxon. Hasil uji Wilcoxon terdapat efektifitas senam knee chest position terhadap kehamilan sungsang dengan nilai signifikansi 0,05 yaitu 0,001 di Klinik Ar-Rahim Kec. Carenang Kab. Serang Banten tahun 2023. Penelitian ini diharapkan bisa diaplikasikan tentang penanganan kehamilan sungsang dengan menggunakan senam knee chest position sebagai upaya merubah posisi janin menjadi normal pada diri sendiri, keluarga, maupun kerabat. Kata Kunci: Senam, Knee Chest, Ibu Hamil Letak Sungsang